Analysis of blood flow, pressure and velocity in a Stented Abdominal Aortic Aneurysm model - Nur Farahiyah, Mohammad; M.N Nassriq; Saidatul Ardeenaawatie, Awang (Universiti Malaysia Perlis, 2009)
Organized by School of Mechatronic Engineering (UniMAP) & co-organized by The Institution of Engineering Malaysia (IEM), 11th - 13th October 2009 at Batu Feringhi, Penang, Malaysia.